Konstruksi Sosial Keagamaan Masyarakat Pada Masa Pandemi Covid-19 - Putri Nadhiyatul Firdausi; Abdul Ghofur; Bambang Subahri (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
Covid-19 or Corona pandemic, which has entered Indonesia since the last three months, has changed many of the religious behaviors of Indonesian people who are predominantly Muslim. Starting from praying in congregation at home, Friday prayers at home, Eid prayer at home, changing sentences on some words in the call to prayer to cancel the departure of the pilgrims. This has changed the religious traditions and religious behavior of the community in general. This study uses theoretical conceptions according to Peter L. Berger with the conception of social construction with three components, namely externalization, objectivation and internalization. This study uses a qualitative approach with the aim of uncovering a phenomenon of religious behavior that occurred in the community during the Covid-19. The conclusions in this research are, externally the community made social changes because of information related to the Covid-19 pandemic, both through a task force formed by the government, as well as news that circulated on television and social media. From that, people make objectivation by implicit behavior formation in response to government regulations and news circulating on social media. Internalization is carried out by the public by picking wisdom in every situation that occurs. Furthermore, from the socio-religious construction the perspective of Sufism during the pandemic resulted in patterns of religious behavior: patient, gratitude, tawakal and muhasabah Keywords: Covid-19, Social Construction, Tasawuf, Society